Pediatric Hepatitis and Respiratory Viruses: A Spatiotemporal Ecologic Analysis. Issue 4 (8th February 2023) - Sawires, Rana; Osowicki, Joshua; Clothier, Hazel; Fahey, Michael; Buttery, Jim
Abstract : Introduction: Beginning in early 2022, clusters of severe pediatric hepatitis were reported in Europe and the United States. To date, no cause has been identified although human adenovirus 41 has been proposed in a proportion of cases. We examined population data >11 years for hepatitis clusters in Victoria, Australia, and whether any were spatiotemporally associated with community transmission of common respiratory viruses. Methods: We used SaTScan to analyze for clusters of pediatric hepatitis and respiratory adenoviruses in Victoria. Negative binomial regression analysis was performed to determine any associations between hepatitis and respiratory viruses across Victoria between July 1, 2011, and June 30, 2022. Results: A number of positive associations were observed in Victoria between pediatric hepatitis clusters and respiratory viruses in our spatiotemporal analysis. A positive association was not found with respiratory adenoviruses or SARS-CoV-2. Increased hepatitis clusters were observed in 2021 and 2022 as noted internationally. Conclusion: The current hepatitis outbreak is novel and, although respiratory viruses are broadly associated with hepatitis, SARS-CoV-2 and respiratory adenoviruses are unlikely to be related.